THE USAGE OF SOCIAL NETWORKS IN TEACHING A FOREIGN LANGUAGE - Safarov Jonibek Anvar ugli; Nasirov Abdurakhim Abdimutalipovich (American Journals, 2023)
This article discusses how to use various intelligence technologies, Internet services, and social networks in teaching a foreign language. Facebook, being the world's largest social network, is given special attention. The great academic potential of the social network Facebook in the modernization of the educational process is also discussed in this article.
Keywords: Internet resource; Web site; technological barrier, information technology tool; software; network etiquette.